ChemInform Abstract: Direct Synthesis of 2‐Arylbenzothiazoles from Benzothiazoles with Phenylglycine Derivatives Mediated by Cu(OTf)2/K2S2O8. Issue 33 (August 2015) - Wang, Rui; An, Chun‐hong; Li, Yang; Zhao, Yue; Wang, Tao; Li, Ao
Abstract The reaction tolerates various functional groups in both partners and affords 2‐arylbenzothiazoles in moderate to good yields.